Perbaikan Barrier Gate MX-50 di PT. ASDP Indonesia Ferry Cabang Merak - Susilawati Susilawati; Ilham Akbar Darmawan (LPPM Politeknik Pratama, 2023)
With current technological advances that are very rapid, parking bars are increasingly sophisticated, one example is the parking barrier system (Barrier Gate), which currently uses finger prints, cards and buttons to open the parking barrier, and there are many types of parking bars with different features. increasingly sophisticated. The purpose of this research is to find out how the barrier gate mx-50 works, the repairs and maintenance carried out on the barrier gate mx-50. The research method used is observation, interviews with related parties and literature study. The components that have been repaired at the barrier gate are the vehicle loop detector and loop cable because these two components do not detect metal so the barrier arm does not move up. And for the components that are carried out maintenance include the AC motor or gearbox and spring or per.